Analisis Stres Kerja Pegawai Pada PT. Bank X Tbk Kantor Cabang Tanah Abang - Tessalonika Sitinjak; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2023)
In the company, employees are very important assets as a determinant of realizing company goals. Without their active role, the company's goals would be impossible to realize. But not infrequently, companies that still do not pay attention to the work stress of their employees. The purpose of this study was to determine the work stress of employees at PT. Bank X Tbk Tanah Abang Branch Office which includes factors that cause work stress, the impact of work stress, and effective stress management strategies for employees of PT. Bank X Tbk Tanah Abang Branch Office. This study used qualitative research methods with data collection techniques, namely primary and secondary data, and used sampling techniques, namely purposive sampling. The results showed that employees of PT. Bank X Tbk Tanah Abang Branch Office which experiences work stress is caused by various factors and has an impact on employee performance and productivity as well as physical and mental health.